Judicial Application of International Law in Southeast Europe - Rodin, Siniša (Springer, 2016)
This edited volume presents comparative research on how the courts in Southeast Europe apply international law. After the introductory Part I, Part II discusses specific areas of international law, notably the law of Association Agreements between the EU and third countries, the law of the World Trade Organization, and international environmental law (the Aarhus Convention). Part III consists of country reports on how national courts in Albania, Bosnia and Herzegovina, Croatia, Kosovo, Macedonia, Montenegro, Serbia and Slovenia are currently applying international law.